Iron catalyst with low metal content, high carbon deposition resistance and stable structure, preparation method and application of iron catalyst in direct dehydrogenation of ethylbenzene

By using the gel method to prepare iron catalysts with low metal content and high carbon deposit resistance in ethylbenzene dehydrogenation catalysts, the high cost and high energy consumption problems caused by the high use of rare earth elements and severe carbon deposits of existing catalysts are solved. Achieve low-cost and low-energy-consuming catalyst applications.

CN119455962APending Publication Date: 2025-02-18TIANJIN DAGU CHEM CO LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411591248.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing ethylbenzene dehydrogenation catalysts have high costs due to the high use of rare earth elements, and the serious carbon deposits of the catalysts lead to high water-hydrogen ratio and serious potassium loss, which in turn leads to the problem of high energy consumption in production.

Method used

Design and prepare an iron catalyst with low metal content, high carbon deposit resistance and stable structure. The gel preparation process is adopted to change the existence and form of iron and additives, reduce the amount of iron and additive elements, and pass the batch method to pass Oxygen or air releases the catalyst to regenerate, reducing the use of water vapor.

Benefits of technology

In the direct dehydrogenation reaction of ethylbenzene, the metal usage and production cost of the catalyst are reduced, the water-hydrogen ratio and potassium loss are reduced, and the catalyst's resistance to carbon deposits and stability are improved, thereby reducing operating energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455962A_ABST
    Figure CN119455962A_ABST
Patent Text Reader

Abstract

The invention discloses an iron catalyst with low metal content, high carbon deposition resistance and stable structure, a preparation method and application of the iron catalyst in direct dehydrogenation of ethylbenzene, and belongs to the technical field of catalysts. The ethylbenzene dehydrogenation gel catalyst contains the elements of aluminum, iron, potassium, cerium and oxygen, and is a high-strength gel catalyst which takes aluminum oxide as a main framework and internally contains highly dispersed iron, potassium and cerium species; the preparation method comprises the following steps: firstly, designing and preparing a novel high-strength and high-dispersion iron catalyst, changing the existence forms of iron and auxiliaries, and meanwhile, reducing the dosage of iron and auxiliary elements; secondly, the nature that the surface of iron oxide is easy to coke and deposit carbon is fundamentally changed, the amount of deposited carbon is reduced under the condition of the same yield, more easily removed deposited carbon types are formed, and effective components (such as potassium) are ensured not to be lost; carbon deposition is eliminated by a milder regeneration means, so that the catalyst is regenerated, and the operation energy consumption of ethylbenzene dehydrogenation is reduced on the whole; therefore, the method has the advantages of lower operation cost, energy conservation and consumption reduction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to an iron catalyst with low metal content, high resistance to carbon deposition and stable structure, a preparation method and application thereof in direct dehydrogenation of ethylbenzene. Background Art

[0002] The catalytic dehydrogenation of ethylbenzene to produce styrene is an important industrial reaction. At present, the reaction generally uses a potassium-promoted iron oxide catalyst, which is carried out under high temperature, low pressure, and a large amount of superheated steam. In addition to being a heat source and a diluent to reduce the partial pressure of ethylbenzene, the role of water vapor is to remove carbon deposits on the surface of the catalyst. Due to the rapid carbon deposition rate of the current iron oxide catalyst, a large amount of water vapor is required, resulting in high energy consumption in the production process, large product condensation volume, and high process equipment costs, which makes the production cost high. Therefore, trying to reduce the amount of water vapor, that is, reducing the water-to-hydrocarbon ratio, is one of the important measures for energy saving and consumption reduction of styrene devices. That is, if the catalyst's ability to resist carbon deposition can be improved, or the rate of carbon deposition of the catalyst can be slowed down, the consumption of water vapor or other gases required to eliminate carbon deposition will be greatly reduced, thereby fundamentally achieving energy saving and consumption reduction. On the other hand, the large-scale use of water vapor makes the problem of potassium loss not to be ignored. At present, potassium is regularly supplemented in industry to maintain the performance of the catalyst.

[0003] By consulting the published patents, it can be found that the current ethylbenzene dehydrogenation is still mostly focused on optimizing the formula, that is, changing the composition of elements. In order to reduce the water-hydrocarbon ratio, the Shanghai Petrochemical Research Institute of Sinopec has conducted a lot of research and added Eu 2 O 3 , Tb 2 O 3 and Ho 2 O 3 Other methods include adding rare earth metal oxides (CN106582681A), or adding cerium oxide with a (111)-based crystal face composition (CN115957775A). Suzhou Toruite Company has also conducted many studies on reducing the water-hydrocarbon ratio, such as adding more alkali metal oxides Na 2 O(CN106927997A). China National Petroleum Corporation converts alkali metal oxide Rb 2 O、Cs 2O is modified on the catalyst surface by impregnation or spraying in the form of nitrate solution (CN105749934A). The common feature of these patents is that they still use iron oxide as the main component, and the water-to-hydrocarbon ratio is reduced to a certain extent through the optimization of additives. We also note that although the amount of water vapor is reduced, the problem of potassium loss associated with the use of water vapor still exists, resulting in a decrease in catalyst activity and an increase in carbon deposition rate. Therefore, while reducing the water-to-hydrocarbon ratio, reducing potassium loss is also another issue of concern at present. For example, Shanghai Petrochemical Research Institute introduced potassium silicate species into the catalyst, which reduced the loss of potassium and was able to operate stably under conditions of a lower water-to-hydrocarbon ratio (CN109569637A).

[0004] In addition, in view of the high cost of rare earth metals as additives, in order to reduce the cost of catalysts, some researchers are committed to reducing the amount of rare earth element cerium. For example, Shanghai Petrochemical Research Institute prepared a catalyst with low cerium content by adding Nb and Zr elements (CN105749934A); and used the interaction between Zn and Ga, Sn, and Bi elements in the additive to improve the stability of the low cerium catalyst (CN106582674A).

[0005] In addition, the strength of the catalyst is also a concern of researchers. At present, in the process of forming a catalyst with iron oxide as the main component, it is necessary to add binders such as kaolin and silicate cement (CN104525213A). Sinopec Corporation has found that the addition of binders is not conducive to the dispersion of the active phase in the catalyst, nor is it conducive to the water-gas reaction between water vapor and surface carbon (CN115869961A). Suzhou Toruite Company first mixes the catalyst raw material with deionized water to form a viscous paste by adding sodium compounds and manganese compounds, and then dries and roasts it, and proposes a high-strength catalyst without adding a binder (CN106994353A). Research by the Dalian Institute of Chemical Physics, Chinese Academy of Sciences shows that the use of a sol-gel method to prepare a precursor for a catalyst carrier for the Fischer-Tropsch synthesis reaction can achieve the effect of obtaining a high-strength catalyst without using a binder (CN202210111944.0). LG Chem Co., Ltd. of Japan also prepared a ferrite catalyst for the oxidative dehydrogenation of butene to butadiene through a sol-gel method (CN201880002321.1).

[0006] From the above research progress, it can be seen that one of the research focuses on potassium-promoted iron oxide catalysts is energy saving and consumption reduction, such as reducing the water-hydrocarbon ratio and reducing potassium loss; the second research focus is to reduce the cost of the catalyst, such as the use of rare earth elements; the third research focus is to optimize the molding method of high-strength catalysts. Therefore, in response to the above problems, the development of more energy-saving and lower-cost high-strength ethylbenzene dehydrogenation catalysts still has great application prospects. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide an iron catalyst with low metal content, high resistance to carbon deposition and stable structure, a preparation method and application thereof in direct dehydrogenation of ethylbenzene, in view of the high catalyst cost caused by the high use of rare earth elements in the current ethylbenzene dehydrogenation production, the high water-to-hydrocarbon ratio and potassium loss caused by severe carbon deposition on the catalyst, and the high energy consumption in production caused by the high water-to-hydrocarbon ratio and potassium loss caused by severe carbon deposition on the catalyst.

[0008] In order to solve the above technical problems, the present invention first designs and prepares a new type of high-strength, highly dispersed iron catalyst, changes the existence form of iron and auxiliary agents, and reduces the dosage of iron and auxiliary elements; secondly, fundamentally changes the nature of the iron oxide surface that is easy to coke and deposit, reduces the amount of carbon deposits under the condition of equal output, forms a type of carbon deposits that is easier to remove, and ensures that effective ingredients (such as potassium) are not lost; and finally, a milder regeneration method is used to eliminate carbon deposits and regenerate the catalyst, thereby reducing the operating energy consumption of ethylbenzene dehydrogenation as a whole.

[0009] The elements contained in the ethylbenzene dehydrogenation gel catalyst of the present invention are aluminum, iron, potassium, cerium and oxygen. It is a high-strength gel catalyst with aluminum oxide as the main skeleton and highly dispersed iron, potassium and cerium inside. Calculated by taking the sum of mass percentage as 100%, the content of each element is as follows:

[0010] 85%~93.8% aluminum, in the form of Al 2 O 3 count;

[0011] 5% to 12% iron, as Fe 2 O 3 count;

[0012] 1% to 5% potassium, as K 2 O meter;

[0013] 0.2% to 2% cerium, as CeO 2 count.

[0014] The method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure described in the present invention adopts a gel method different from the traditional mixing method, and the steps are as follows:

[0015] 1) Anhydrous ethanol and deionized water are mixed to prepare a mixed solvent A;

[0016] 2) dissolving aluminum salt, iron salt, potassium salt and cerium salt in the mixed solvent A obtained in step 1), stirring and heating to obtain a mixed salt solution B;

[0017] 3) cooling the mixed salt solution B obtained in step 2) to room temperature, and slowly dripping the epoxy gel accelerator at a constant rate under a certain temperature and sufficient stirring to form a semi-gel;

[0018] 4) transferring the semi-gel obtained in step 3) into a thermostatic bath to further promote gel formation at a certain temperature to obtain a wet gel precursor C;

[0019] 5) sealing the wet gel precursor C obtained in step 4) with ethanol and aging it at room temperature for a certain period of time;

[0020] 6) Drying and calcining the wet gel precursor C after aging in step 5) to obtain the iron catalyst with low metal content, high resistance to carbon deposition and stable structure.

[0021] In step 1), the volume ratio of anhydrous ethanol to deionized water is 1 to 4:1, preferably 2:1;

[0022] In step 2), the aluminum salt, iron salt, potassium salt and cerium salt are one or two of chloride and acetate, preferably chloride; in order to maintain the gel strength, the molar concentration of aluminum ions in the mixed salt solution B is 0.6-1.5 mol / L (preferably 0.8-1.2 mol / L), the molar concentration of iron ions is 0.035-0.15 mol / L, the molar concentration of potassium ions is 0.014-0.07 mol / L, and the molar concentration of cerium ions is 0.001-0.007 mol / L; the heating temperature is 40-90° C., preferably 60-80° C.; the heating time is 15-60 min; and the stirring speed is 200-500 r / min;

[0023] In step 3), 15-20 mL of epoxy gel accelerator is dripped into 30 mL of mixed salt solution B; the temperature range of dripping the epoxy gel accelerator is 0-10° C., preferably 0-5° C.; the epoxy gel accelerator is one of propylene oxide, epichlorohydrin, and 1,2-butylene oxide; the dripping speed is 3-10 mL / min;

[0024] In step 4), the temperature for further promoting gel formation is 50 to 80° C., preferably 60 to 70° C.; the time for promoting gel formation is 3 to 10 minutes;

[0025] In step 5), the aging time is 12 h to 72 h, preferably 24 to 48 h;

[0026] In step 6), the drying temperature is 30-80°C, preferably 55-65°C; the calcination temperature is 600-900°C, preferably 700-800°C; the calcination atmosphere is pure oxygen or air atmosphere; the calcination time is 1-8h, preferably 4-6h.

[0027] The iron catalyst with low metal content, high resistance to carbon deposition and stable structure described in the present invention is prepared by the above method.

[0028] The iron catalyst with low metal content, high resistance to carbon deposition and stable structure prepared by the present invention can be used in the direct dehydrogenation of ethylbenzene. According to the particle size of the gel catalyst after crushing, it can be used in a fixed bed reactor or a fluidized bed reactor, and the catalyst can be regenerated by intermittent oxygen or water vapor. The method of regenerating the catalyst by intermittent oxygen or water vapor is considered to save energy to the greatest extent. The present invention does not exclude the method of continuous reaction of introducing water vapor or air while introducing ethylbenzene, but in view of the presence of water vapor or air, the activity of the catalyst is slightly inhibited, which is not considered to be the best way to use the gel catalyst of the present invention.

[0029] The iron catalyst with low metal content, high resistance to carbon deposition and stable structure can be used in direct dehydrogenation of ethylbenzene. The reaction pressure is negative pressure or normal pressure (1 standard atmospheric pressure is normal pressure), the reaction temperature is 550-610°C, and the ethylbenzene space velocity is 0.1-10h -1 There is no special requirement for the flow rate and time of air or water vapor used for regeneration, as long as it can restore the activity of the catalyst.

[0030] Features and advantages of the present invention:

[0031] (1) The catalyst of the present invention is based on alumina as the main skeleton, and contains highly dispersed iron, potassium, and cerium (from Figure 1 It can be seen from the XRD of Example 1 that, except for aluminum oxide, no characteristic peaks of iron oxide, cerium oxide, and potassium oxide are observed, so it is believed that the three are all highly dispersed gel catalysts; due to the high dispersion, the utilization rate of metal iron, potassium, and cerium is high, so the metal dosage is low and the cost is low;

[0032] (2) The catalyst of the present invention does not require the addition of an additional binder or a complicated molding process during its preparation process, and a high-strength catalyst can be obtained by only using an appropriate gel preparation process;

[0033] (3) The catalyst of the present invention has a strong ability to resist carbon deposition and a low carbon deposition rate, and can operate for a long time under the condition of direct dehydrogenation of ethylbenzene without water vapor. Moreover, the carbon deposition type is easy to eliminate and can be directly calcined with air at the reaction temperature or below the reaction temperature to restore the activity of the catalyst. The loss of metal components, especially potassium, can be ignored. Therefore, compared with the existing iron oxide catalyst, the operating cost is lower and it has the advantages of energy saving and consumption reduction. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The XRD analysis spectra of the catalysts prepared in Example 1 and Comparative Example 5; the green line in the figure is the Al 2 O 3 Standard XRD spectrum of Fe (PDF#10-0425); the blue spectrum in the figure is the standard database of Fe 2 O 3 Standard XRD spectrum of (PDF#33-0664); the purple line is K 2 O standard XRD spectrum (PDF#23-0493); the orange spectrum is CeO in the standard database 2 Standard XRD spectrum of (PDF#34-0394).

[0035] Figure 2 This is the air thermogravimetric analysis curve after the reaction of the catalyst prepared in Example 1. It can be seen that the weight loss before 300°C is mainly attributed to the loss of moisture and other adsorbed substances adsorbed by the catalyst; 350-450°C is the temperature range with the fastest weight loss, which is attributed to the burning of surface carbon by air.

[0036] Air thermogravimetric determination method: weigh 20 mg of sample, air flow rate 50 mL / min, heating rate 10°C / min, from room temperature to 750°C.

[0037] Figure 3 This is the air thermogravimetric analysis curve of the industrial BASF catalyst after the reaction of comparative example 6. It can be seen that this curve is different from the thermogravimetric analysis curve of the catalyst of the present invention. The weight loss before 350°C is mainly due to the loss of moisture and other adsorbed substances adsorbed by the catalyst; but the increase in catalyst mass at 350-535°C is due to the Fe in the catalyst. 2+ Oxidized to Fe 3 + The subsequent weight loss at 535-800°C is attributed to the carbon deposits with a high degree of graphitization on the catalyst surface being burned off by air.

[0038] Figure 4 N is the catalyst prepared in Example 1 2Isothermal adsorption-desorption curve. It can be seen that the type of adsorption-desorption hysteresis loop in the figure is roughly H1 type, so the shape of the pores inside the catalyst is close to cylindrical.

[0039] Figure 5 This is the pore size distribution curve of the catalyst prepared in Example 1. It can be seen that the pore size inside the catalyst is concentrated in the range of 10 to 20 nm.

[0040] Table 1: XRF analysis of the mass percentage of each metal element in Example 1 before and after the catalyst reaction and after water treatment (%)

[0041] Metal elements (as oxides) Before reaction After the reaction After water supply <![CDATA[Al 2 THE 3 ]]> 88.67 88.52 88.54 <![CDATA[Fe 2 THE 3 ]]> 6.45 6.47 6.41 <![CDATA[K 2 The]]> 3.04 3.02 3.07 <![CDATA[CeO 2 ]]> 0.81 0.78 0.84

[0042] XRF determination method: 5 grams of catalyst sample is mixed with a few drops of anhydrous ethanol, ground, pressed into tablets, and measured with an X-ray fluorescence spectrometer. The content of each element in the sample to be tested is calculated based on the calibration curve of the intensity of each element in the standard sample. DETAILED DESCRIPTION

[0043] Example 1

[0044] 1) Anhydrous ethanol and deionized water are mixed to prepare a mixed solvent A, the volume of the mixed solvent A is 30 mL, and the volume of anhydrous ethanol to deionized water is 2:1;

[0045] 2) 7.24 g aluminum chloride hexahydrate, 0.34 g ferric chloride hexahydrate, 0.10 g potassium chloride and 0.03 g cerium chloride heptahydrate were dissolved in the mixed solvent A obtained in step 1) to make the theoretical content of each component in the obtained catalyst be Al 2 O 3 : 90.2%,Fe 2 O 3 : 6%, K 2 O: 3%, CeO 2 : 0.8%; heating and stirring at 80°C for 0.5h, with a stirring speed of 300r / min, to obtain a mixed salt solution B;

[0046] 3) cooling the mixed salt solution B obtained in step 2) to room temperature, and dripping 18 mL of propylene oxide gel accelerator thereinto at a constant rate of 5 mL / min per second in an ice water bath at 3° C. with sufficient stirring to form a semi-gel;

[0047] 4) transferring the semi-gel obtained in step 3) to a thermostatic bath and placing it in a 65° C. constant temperature water bath for 5 min to obtain a wet gel precursor C;

[0048] 5) adding 10 ml of anhydrous ethanol to the wet gel precursor C obtained in step 4) for liquid sealing (i.e., using anhydrous ethanol to completely cover the surface of the wet gel precursor C), and aging at room temperature for 36 h;

[0049] 6) After the aging in step 5) is completed, the wet gel precursor C is dried in an oven at 60°C for 12 hours, and then calcined in a muffle furnace at 800°C for 5 hours in an air atmosphere at a heating rate of 2°C / min, thereby obtaining 1.78 g of the block solid iron catalyst, the content of which is shown in Table 1 [Note: The metal content measured by XRF is consistent with the theoretical content (Al 2 O 3 : 90.2%,Fe 2 O 3 : 6%, K 2 O: 3%, CeO 2 :0.8%), which is slightly different from the instrument test accuracy and the loss of chloride ions during the experiment causing slight changes in the content of other elements]; crush and sieve to take 20-40 mesh catalyst for catalytic reaction.

[0050] In addition, the crushing strength was measured according to the technical requirements of standard HG / T2782-1996, using a particle strength tester of model SKZ-500, with 30 particles as a group, and the arithmetic average was taken. The crushing strength of the catalyst of Example 1 was measured to be 35 N / mm.

[0051] The prepared catalyst was used in the direct dehydrogenation reaction of ethylbenzene and the product analysis method was as follows: saturated ethylbenzene vapor at 76°C was brought out by bubbling 10 mL / min of high-purity nitrogen through the bed of a fixed bed reactor with an inner diameter of 8 mm filled with catalyst. The catalyst loading was 0.4 g and the ethylbenzene space velocity was 1.0 h -1 , the reaction temperature is 600℃. The outlet product is absorbed by ethanol, and its composition is analyzed by Shimadzu GC-2010 gas chromatography, and the ethylbenzene conversion rate and styrene selectivity are calculated. Among them, ethylbenzene conversion rate = moles of ethylbenzene consumed / moles of ethylbenzene entered; styrene selectivity = moles of styrene generated / moles of ethylbenzene consumed.

[0052] For the catalyst of Example 1, the ethylbenzene conversion rate in the stable reaction stage was measured to be 60%, the styrene selectivity was 92%, and the catalyst could be stably operated for more than 50 hours. The mass of carbon on the catalyst surface was calculated according to the weight gain after the reaction. After the catalyst of Example 1 was operated for 50 hours, the catalyst gained 0.06g.

[0053] Example 2

[0054] Compared with Example 1, the only difference is that the ratio of aluminum, iron, potassium and cerium in the raw materials remains unchanged, but the mass of the raw materials is reduced to half of the original (the theoretical content percentage of each metal in the obtained catalyst is Al 2 O 3 : 95%,Fe 2 O 3: 3%, K 2 O: 1.6%, CeO 2 :0.4%). The obtained catalyst was still tested for performance using the method of Example 1. For the catalyst of Example 2, the ethylbenzene conversion rate in the stable reaction stage was 45%, the styrene selectivity was 93%, and the catalyst could be stably operated for more than 50 hours.

[0055] Example 3

[0056] Compared with Example 1, the amounts of aluminum, iron and potassium in the raw materials remain unchanged, but the mass of cerium is increased to twice that of Example 1 (the theoretical content percentage of each metal in the obtained catalyst is Al 2 O 3 : 89.4%,Fe 2 O 3 : 6%, K 2 O: 3%, CeO 2 :1.6%). The obtained catalyst was still tested for performance using the method of Example 1. For the catalyst of Example 3, the ethylbenzene conversion rate in the stable reaction stage was 58%, the styrene selectivity was 91%, and it could run stably for more than 50 hours.

[0057] Example 4

[0058] Compared with Example 1, the amounts of aluminum, iron and cerium in the raw materials remain unchanged, but the mass of potassium is increased to 1.5 times that of Example 1 (the theoretical content percentage of each metal in the obtained catalyst is Al 2 O 3 : 88.7%,Fe 2 O 3 : 6%, K 2 O: 4.5%, CeO 2 :0.8%). The obtained catalyst was still tested for performance using the method of Example 1. For the catalyst of Example 4, the ethylbenzene conversion rate in the stable reaction stage was 57%, the styrene selectivity was 93%, and the catalyst could be stably operated for more than 50 hours.

[0059] Example 5

[0060] Compared with Example 1, the catalyst conditions used are the same; the only difference in the reaction conditions is that the catalytic reaction temperature is fixedly set to 575°C, and the rest are not adjusted. The measured performance of the catalyst is: ethylbenzene conversion rate 47%, styrene selectivity 97%, and it can run stably for more than 50 hours.

[0061] Example 6

[0062] Compared with Example 1, the catalyst conditions used are the same; the only difference in the reaction conditions is that the catalytic reaction temperature is fixedly set to 610°C, and the rest are not adjusted. The measured performance of the catalyst is: ethylbenzene conversion rate 65%, styrene selectivity 89%, and it can run stably for more than 50 hours.

[0063] Example 7

[0064] When the catalyst of Example 1 runs to 100h, the ethylbenzene conversion rate drops to 52%. The ethylbenzene feed is switched to 30mL / min of air, the reactor temperature remains unchanged, and after 3 hours of air regeneration treatment, the ethylbenzene feed is switched back. After 1h of adjustment, the ethylbenzene conversion rate rises back to 60% and continues to run smoothly. When the ethylbenzene conversion rate drops to 52% again, air regeneration is performed again. After multiple cycle experiments, the catalyst can be restored to the initial state. It shows that the intermittent regeneration of the catalyst with air will not destroy the physical and chemical properties of the catalyst and is a feasible regeneration method.

[0065] Comparative Example 1

[0066] Compared with Example 1, the only difference is that in the preparation process of the gel catalyst, step 3) is not carried out in an ice-water bath, but at 60° C. We noticed that during the continuous dropwise addition of propylene oxide, the formation of the upper and lower gel layers was obviously uneven, and a complete and uniform gel could not be obtained.

[0067] Comparative Example 2

[0068] Compared with Example 1, the only difference is that, while keeping the ratio of aluminum, iron, potassium and cerium unchanged, the respective raw materials are changed to corresponding nitrates. In step 3), since the solubility of aluminum nitrate is greatly affected by temperature, the aluminum nitrate in the solution is re-precipitated in the ice water bath, resulting in that the aluminum ion concentration in the actual solution cannot meet the requirements, and the strength of the generated gel is very low.

[0069] Comparative Example 3

[0070] Compared with Example 1, the only difference is that potassium salt is removed from the raw material, and the other preparation steps are consistent with Example 1 (the theoretical content percentage of each metal in the obtained catalyst is Al 2 O 3 : 93%,Fe 2 O 3 : 6.2%, CeO 2 :0.8%). The obtained catalyst was still tested by the method of Example 1. The performance of the catalyst was measured as follows: ethylbenzene conversion rate 60%, styrene selectivity 93%, but the stabilization time was significantly shortened and the catalyst could run stably for 12 hours.

[0071] Comparative Example 4

[0072] Compared with Example 1, the only difference is that the mass of aluminum salt added to the raw material is reduced to half of the original, while the volume of the solution remains unchanged. At this time, the aluminum ion concentration in the mixed salt solution B is about 0.5 mol / L. The remaining raw material addition amounts and preparation steps remain unchanged (the theoretical content percentage of each metal in the obtained catalyst is Al 2 O 3 : 82%,Fe 2 O 3 : 11%, K 2 O: 5.5%, CeO 2 :1.5%). During the preparation process, it takes a long time for the gel to form, and the appearance is almost transparent. Compared with Example 1, the mechanical strength of the finished catalyst after drying and calcination is significantly reduced, and the crushing strength is 16N / mm. It is easy to pulverize and is not suitable for use as a fixed bed catalyst.

[0073] Comparative Example 5

[0074] Compared with Example 1, the only difference is that the mass of the iron salt in the raw material is increased to 2.5 times, and the other conditions remain unchanged (the theoretical content percentage of each metal in the obtained catalyst is Al 2 O 3 :81.5%,Fe 2 O 3 : 15%, K 2 O: 2.8%, CeO 2 :0.7%). The obtained catalyst was tested for performance by the method of Example 1. The performance of the catalyst was: 30% ethylbenzene conversion, 91% styrene selectivity, and stable operation for 15 hours. The increase in the amount of iron salt significantly shortened the stable time.

[0075] Comparative Example 6

[0076] At present, BASF catalyst is widely used in the conventional ethylbenzene dehydrogenation industry. The catalyst was tested for the performance of direct ethylbenzene dehydrogenation under the same experimental conditions as in Example 1. The performance of the catalyst was measured as follows: 40% ethylbenzene conversion rate and 93% styrene selectivity. However, the catalyst could not be maintained for a long time and was deactivated after about 10 hours. After running for 10 hours, the catalyst gained 0.12 g.

[0077] XRD analysis of the catalysts prepared by Example 1 and Comparative Example 5 (see Appendix Figure 1) It can be seen that, in the low-content iron gel catalyst of the present invention, except for the aluminum oxide crystal phase, no crystal phases of iron oxide, cerium oxide and potassium oxide can be seen. However, the high-content iron gel catalyst (Comparative Example 5) has an obvious iron oxide crystal phase. In addition, the catalyst with iron oxide as the main component currently used in industry is reported to form potassium ferrite component with potassium oxide, which can be detected by XRD. Compared with the potassium ferrite XRD spectrum in the literature (Li Xiaoci, Journal of Advanced Chemistry, 2017, 38 (7): 1229-12347), the catalyst of Example 1 did not observe the potassium ferrite crystal phase. Therefore, in the low-content iron gel catalyst of the present invention, the iron exists in the form of highly dispersed iron species in the crystalline aluminum oxide skeleton, and its catalytic mechanism is also different from that of traditional iron oxide catalysts. Therefore, the type and amount of carbon deposits produced are significantly different from those of traditional catalysts. The evidence is as follows: (1) From the air thermogravimetric analysis curve of the catalyst of Example 1 after the reaction ( Figure 2 ) It can be seen that the air decomposition temperature range of the carbon deposit on the surface of the low-content iron gel catalyst of the present invention is 400-500°C, which is a type of carbon deposit that is easier to eliminate. In comparison, the air decomposition temperature range of the carbon deposit on the surface of the traditional iron oxide catalyst is 535-650°C, which is a type of carbon deposit that is more difficult to eliminate. (2) Comparing the surface carbon deposit amount of the catalyst of the present invention (Example 1) and the industrial BASF catalyst (Comparative Example 6), it can be seen that the weight gain of the catalyst of Example 1 after the reaction is much lower than that of Comparative Example 6, indicating that the surface carbon deposit amount of the iron catalyst of the present invention is relatively less and has better resistance to carbon deposition.

[0078] In addition, after 100h of reaction, the catalyst of the present invention was calcined with air to remove the carbon on the surface, and then the element content of the catalyst of Example 1 was analyzed by X-ray fluorescence spectrometry (XRF) (see Table 1), and no obvious potassium loss was found. This is related to the process of using air instead of water vapor to remove carbon in the present invention. In order to prove that the potassium of the catalyst of the present invention is not easy to lose even with water vapor, we did a test of passing water for 50h alone, and did XRF analysis on the samples before and after the water treatment (see Table 1), and no potassium loss was found, which fully proves the important role of the preparation method of the present invention in fixing the effective ingredients. For traditional catalysts, the loss of potassium under the action of water vapor is inevitable (as mentioned in patents CN105669355A and CN104888817A).

[0079] The catalyst of the present invention can be used for direct dehydrogenation of ethylbenzene without water vapor during use, and can be supplemented by a regeneration process of intermittent air roasting and carbon removal to achieve the purpose of maximum energy saving.

[0080] From the above embodiments and comparative examples, it can be seen that the control of the process parameters of the gel preparation method (especially the temperature of the ice-water bath to form a semi-gel and the content of each element) is the key to obtaining an iron catalyst with low metal content, high resistance to carbon deposition and stable structure in the present invention.

Claims

1. A method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure, the steps of which are as follows: 1) Anhydrous ethanol and deionized water are mixed to prepare a mixed solvent A; 2) dissolving aluminum salt, iron salt, potassium salt and cerium salt in the mixed solvent A obtained in step 1), stirring and heating to obtain a mixed salt solution B; 3) cooling the mixed salt solution B obtained in step 2) to room temperature, and slowly dripping the epoxy gel accelerator at a constant rate under a certain temperature and sufficient stirring to form a semi-gel; 4) transferring the semi-gel obtained in step 3) into a thermostatic bath to further promote gel formation at a certain temperature to obtain a wet gel precursor C; 5) sealing the wet gel precursor C obtained in step 4) with ethanol and aging it at room temperature for a certain period of time; 6) Drying and calcining the wet gel precursor C after aging in step 5) to obtain the iron catalyst with low metal content, high resistance to carbon deposition and stable structure; the content of each element is as follows, calculated based on the mass percentage and 100%: 85% to 93.8% aluminum, calculated as Al2O3; 5% to 12% iron, calculated as Fe2O3; 1% to 5% potassium, calculated as K2O; 0.2% to 2% cerium, calculated as CeO2.

2. The method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 1, characterized in that: In step 1), the volume ratio of anhydrous ethanol to deionized water is 1 to 4:

1.

3. The method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 1, characterized in that: In step 2), the aluminum salt, iron salt, potassium salt and cerium salt are one or two of chloride and acetate, the molar concentration of aluminum ions in the mixed salt solution B is 0.6-1.5 mol / L, the molar concentration of iron ions is 0.035-0.15 mol / L, the molar concentration of potassium ions is 0.014-0.07 mol / L, and the molar concentration of cerium ions is 0.001-0.007 mol / L; the heating temperature is 40-90° C., the heating time is 15-60 min, and the stirring speed is 200-500 r / min.

4. The method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 1, characterized in that: In step 3), 15 to 20 mL of epoxy gel accelerator is dripped into 30 mL of mixed salt solution B; the temperature range of dripping the epoxy gel accelerator is 0 to 10° C.; the epoxy gel accelerator is one of propylene oxide, epichlorohydrin, and 1,2-butylene oxide, and the dripping speed is 3 to 10 mL / min.

5. The method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 1, characterized in that: In step 4), the temperature for promoting gel formation is 50 to 80° C., and the time for promoting gel formation is 3 to 10 minutes.

6. The method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 1, characterized in that: In step 5), the aging time is 12 h to 72 h.

7. The method for preparing an iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 1, characterized in that: In step 6), the drying temperature is 30-80° C., the calcination temperature is 600-900° C., the calcination atmosphere is pure oxygen or air atmosphere, and the calcination time is 1-8 hours.

8. An iron catalyst with low metal content, high resistance to carbon deposition and stable structure, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 8 in direct dehydrogenation of ethylbenzene.

10. Use of an iron catalyst with low metal content, high resistance to carbon deposition and stable structure as claimed in claim 9 in direct dehydrogenation of ethylbenzene, characterized in that: The reaction pressure is negative pressure or normal pressure, the reaction temperature is 550-610℃, and the ethylbenzene space velocity is 0.1-10h -1 .

Citation Information

Patent Citations

  • Method for preparing Fe-K catalyst for ethylbenzene dehydrogenation from mixed iron source

    CN104525213A

  • Low-water-ratio ethylbenzene dehydrogenation catalyst

    CN104888817A

  • Process for preparation of styrene from ethylbenzene

    CN105669355A

  • Catalyst used for low steam-to-oil ratio ethylbenzene dehydrogenation to prepare styrene, and preparation method thereof

    CN105749934A

  • Low rare earth catalyst for ethylbenzene dehydrogenation

    CN106582674A